Critical issues facing Indian irrigation - Vaidyanathan, A. (International Food Policy Research Institute, 1990)
The expansion and improvement of irrigation facilities occupy a central place in India's strategy for raising agricultural productivity. Investments in irrigation constitute the single largest component of agricultural investment overall and particularly in the public sector. Over the past forty years, the state spent a total of Rs 435 billion on agricultural and rural development, including irrigation and flood control; investment in irrigation alone totaled Rs 180 billion. The largest part of state expenditure on irrigation went to construct new and rather large surface systems, as well as works to promote quicker and better use of the water made available by these systems. The state also gave a substantial amount of assistance to groundwater development by offering loans and grants to farmers for constructing and energizing wells, by supporting investment in rural electrification, and to a limited degree by setting up public tubewells. Total irrigated area reportedly rose from 22.6 million hectares (17 percent of crop area) in 1950-51 to 54.1 million hectares (31 percent of crop area) in 1984/85.